CCAFS East Africa Impact Pathway Meeting 2014 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
On November 17th -19th 2014 The CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS), East Africa held an Impact Pathway planning meeting at the Hemmingways Hotel, Nairobi. The meeting brought together all project, presenting a valuable opportunity to create synergies among the different projects. Photos: S.Kilungu (CCAFS)